Ions in solution and their solvation - Marcus, Y. (John Wiley & Sons, Inc., 2015)
The book starts with an exposition of the relevant properties of ions and continues with a description of their solvation in the gas phase. The book contains a large amount of factual information in the form of extensive tables of critically examined data and illustrations of the points made throughout. It covers: the relevant properties of prospective liquid solvents for the ions the process of the transfer of ions from the gas phase into a liquid where they are solvated various aspects of the solutions of the ions.